Analisis Break Even Point Terhadap Produksi Ayam Petelur Pada UD. Kakaskasen Indah - Cintia G. M. Worang; Frendy A. O. Pelleng; Henny S. Tarore (Universitas Sam Ratulangi, 2018)
The development of the business in this world it’s so fast, in the field of trade and manufacturing. Trading businesses carry out their activitiesby buying products and selling them back to consumers. Every business that is estabilshed is motivated by various factors, which is the deman or interest of the communtiy towards the products produced by a business to fulfill their needs. Each company needs to know the Break Event point level of each company, including companies engaged in the chicken husbandry sector that produce laying hens like UD. Kakaskasen Indah. Break Even Point is a condition in which the company operations doesn’t mae a profit and also doesn’t have suffer losses. The purpose of this study is (1) to knowing the cost elements calculated in the Break Event point component . (2) to know the number of Break Event points in units and Rupiah at UD. Kakaskasen Indah in 2017. (3) to knowing the size of Margin Safety in 2017 so that UD. Kakaskasen Indah does not suffer losses. The results of this study also show that management of this company can find out the level of Break Event Points. The Break Event point level shows minimun sales laying hens that must be achived by UD. Kakaskasen Indah so as not to suffer losses. The method used in this study is descriptive research. The data sought in this study is a report on egg production costs which will be used to dtermine Break Event point. The resilts of this study is cost obtained is very important, researchers also find the amount of profits that will later be obtained by the company, thi is determained by how much the costs incurred or recived by the company. Based on Break Event points calculation in 2017, UD. Kakaskasen Indah achived a Break Event point on egg sales of Rp. 9.949.539,134 or 254.767,98 units. With Safety od Margin 52,82% so the company does not to suffer losses. Keywords:Break Even Point, Cost, Sales, Profit